Sugarcane-raya intercropping: A promising option to sustain yield and enhance farm profitability (Zoo Botanica, 2025)
Sugarcane is a long-duration and slow-growing crop, which permits the opportunity to cultivate a short-duration crop in the same field during the same season. In this regard, intercropping of a mustard species “Super raya” can be the best option to enhance economic returns and improve overall land productivity. Therefore, a field trial was conducted to evaluate the effect of planting times of sugarcane and planting geometries of raya at Sugarcane Research Station, Khanpur, Rahim Yar Khan, Punjab, Pakistan. Experimental treatments were composed of two planting times of sugarcane (PD1=September 10, 2023, and PD2=October 10, 2023) and planting geometries of raya (S-1R=single row raya, S-2R=double row raya, and S-3R=triple row raya) intercropped within sugarcane. Sole sugarcane (S-Cn) and sole raya (R-3R) were also included as control treatments.  Results of the current study showed that sole raya and sole sugarcane crops showed the maximum yields of 142.6 tons ha-1 (PD1) and 1.8 tons ha-1, respectively, as compared to other tested arrangements. Double row planting geometry of raya within September sugarcane also exhibited greater yield of 134.6 tons’ ha-1 and 1.53 tons ha-1 for sugarcane and raya, respectively. This double row plant geometry within September-sown sugarcane also showed a higher benefit-cost ratio (32.4%) and land equivalent ratio (2.27%) attributed to a lower yield reduction ratio (0.6), greater yield stability index (0.94), and land equivalent ratio (1.80) under this treatment. In conclusion, double-row planting of raya within September-sown sugarcane can be recommended as a profitable agronomic practice for increasing land use efficiency and farm income in arid agro-climatic regions.
Keywords: : Sustainability; sugarcane; super raya; farm income